New Synthesis of Cyclic Imide Compounds for Ampicillin Drug and Studying Their Biological Activity (Baghdad Science Journal, 2025)
Some new cyclic imides are prepared by the reaction of ampicillin drug with different cyclic anhydrides as a first step to form amic acids for ampicillin drug. The second step includes the reaction of prepared amic acids with acetic anhydride and anhydrous sodium acetate with heating in THF as a solvent to give cyclic imide compounds. These compounds are identified by melting points, FT-IR, 1H-NMR, and biological activity